Development of an Escherichia coli optical biosensor with computational validation. Issue 1 (1st December 2022) - Dante, A; Silva, P H; Lopes, R; Allil, A; Sbano, A; Esteves, M E; Silva, M; Werneck, M; Allil, R
Abstract: The biosensor consists of an optical sensing system and an optoelectronic data acquisition system. The sensor's optical system consists of a biochemically functionalized polymer optical fiber (POF-Plastic Optical Fiber) based on Field Evanescent technology. The Evanescent Field technique has been widely adopted in sensing and in this project, it was obtained by bending the fiber in a "U" shape, aiming to increase the sensitivity of the biosensor, through the contact of the curved sensor part with the sample biological. A data acquisition system was developed through an optoelectronic project aiming to increase the sensitivity when compared to a commercial equipment acquisition system. This work presents a biosensor for the detection of Escherichia coli based on an evanescent field with a polymer optical fiber linked to the analog signal acquisition system through an optoelectronic system developed. The interaction investigation of antibodies and antigens in Escherichia coli for computational methods was carried out in order to obtain information about the action of the antibody and in future steps applied in the validation of the diagnostic method.